Business process outsourcing as a key strategy of enterprises in an unstable economic situation - N. N. Trofimova (Управление)
The article considers business process outsourcing from the point of view of the strategic basis for the activities of enterprises in an unstable economy. The paper shows that, presently, the outsourcing strategy is becoming the new norm and is changing the entire world economy. The study uses the author’s approach, based on the methods of scientific generalization, comparative analysis, systemic and situational approach. The paper justifies the application of the outsourcing strategy at enterprises, ascertains the main advantages and disadvantages of its implementation. The author develops a model of enterprise transformation based on business process outsourcing. The study gives recommendations for outsourcing business processes, the implementation of which will allow enterprises to optimize their management strategy in an unstable economic situation. This article can serve as a basis for further research in the field of strategic management based on outsourcing technologies.